Discrimination, Violence and Disregard of Right: Status of Domestic Workers in the Absence of Legal Protection for Domestic Workers - Anita Dhewy (Yayasan Jurnal Perempuan, 2017)
This paper focuses on the experience of domestic workers who experience violence, discrimination and neglect of rights committed by employers as well as management of apartments where domestic workers work. From the data of six domestic workers withdiverse backgrounds who were interviewed in depth, it can be revealed that every domestic worker has experienced violence during work. There are forms of violence that can be easily recognized as violence, but there is also some discrimination and violence that are not viewed as violence or are considered fairness. This type of discrimination and violence is usually associated with inappropriate work situations. The vulnerability situation faced by domestic workers because of the scope of their work in this private domain is an implication of the absence of laws protecting domestic workers in carrying out their work. Therefore, the existence of law as an umbrella law of domestic workers protection as well as other workers becomes a fundamental requirement.